The Transition to a Register-based Production System - Wallgren, Anders; Wallgren, Britt (Register-Based Statistics, 2022)
The transition from a census‐based into a register‐based national statistical system will change the entire production system. This chapter treats some of the main issues that become important when the national statistical office (NSO) in a country starts to systematically work with administrative registers. The starting point for a national statistical office could be that the NSO is responsible for the Population and Housing Census, several area‐based household sample surveys and some business sample surveys. For ministries and other authorities responsible for administrative systems, the new cooperation with statisticians will result in feedback regarding data quality. This feedback can start improvements in administrative systems. The term national registration system refers to all the administrative systems in the public sector that are used to handle the national registration of persons living in the country and their activities.